Answer:
Option a is the correct answer
Step-by-step explanation:
The slope intercept form of an equation is defined as
y = mx + c where
m= the slope of the equation. The slope would be determined by (change in the value of y on the vertical axis) /
(change in the value of x on the horizontal axis)
From the equation given,
y + 6 = 2(x + 2)
We would rearrange this equation so that it will conform with the slope intercept form , y = mx + c as stated earlier.
Opening the brackets,
y + 6 = 2x + 4
Subtracting 6 from both sides of the equation,
y + 6 - 6 = 2x + 4 - 6
y = 2x -2
Comparing with y= mx + c,
The y-intercept is -2
The slope = 2